A cache of jewels and other collective nouns - Heller, Ruth (New York : Scholastic, 1990)
Rhyming text and illustrations introduce a variety of collective nouns such as a "drift of swans" and a "clutch of eggs."
H
Copyright: PUB 1Mar90; PA544-919.
Reference source used: copyright data sheet.
b
b